The Risk Management Committee and Bank Stability: A Proposed Framework - David Fajembola, Olusola; Abdul Rahman, Nora Azureen; Md-Rus, Rohani (Journal of Advanced Research in Business and Management Studies, 2020)
The recent spate of bank crisis in Nigeria and the instability that accompanied it in several banks necessitated the need to find out the underlying cause and proffer solutions. This proposed framework is aimed at examining the roles of the risk committee in the crisis. The objective is to investigate the relationship between the risk management committee and bank stability in Nigeria. The framework presents the attributes of the risk management committee that could have impact on bank stability. It also presents the agency and resource dependence theories as relevant to the investigation. Given that this is a proposed framework, it is subject to review. If it is validated, it would contribute towards providing insight into the roles of the risk management committee in Nigerian banks and aid policy formulation on risk governance.